Technology for preventing work-related musculoskeletal injuries in healthcare professionals: A scoping review - Ana Sofia Teixeira; Maria Joana Campos; Carla Sílvia Fernandes; Marta Campos Ferreira (Tehran University of Medical Sciences, 2024)
Background & Aim: This scoping review aims to identify and summarize how Technology can help in the prevention of work-related Musculoskeletal Injuries of healthcare professionals. Methods & Materials: We conducted a scoping review following the steps provided by the Joanna Briggs Institute. The PRISMA® - Preferred Reporting Items for Systematic Reviews and Meta-Analyses model was used to organize the information, following the recommendations described in PRISMA-ScR (PRISMA Extension for Scoping Reviews) for the article presentation. A search of PubMed, Scopus, and CINAHL databases was conducted for all articles in December 2023. Results: Of the 964 initial articles identified, 7 met the inclusion criteria. The reviewed studies highlight the effectiveness of various technological interventions in reducing musculoskeletal injuries among healthcare professionals. Wearable technologies, such as inertial measurement units, have been effective in promoting correct posture and reducing the risk of musculoskeletal disorders. However, the studies also identified significant challenges, including the generalizability of findings, the need for more robust empirical evidence, and issues related to the long-term sustainability and cost-effectiveness of these technologies. Conclusion: The conclusion of this analysis highlights the need for scalable, effective, and customized therapies and calls for more study and development in gamification, wearable technologies, and tailored mobile applications.